Ferroptosis-mediated immune responses in cancer - Qi, Desheng; Peng, Milin (Frontiers in Immunology, 2023)
Cell death is a universal biological process in almost every physiological and pathological condition, including development, degeneration, inflammation, and cancer. In addition to apoptosis, increasing numbers of cell death types have been discovered in recent years. The biological significance of cell death has long been a subject of interest and exploration and meaningful discoveries continue to be made. Ferroptosis is a newfound form of programmed cell death and has been implicated intensively in various pathological conditions and cancer therapy. A few studies show that ferroptosis has the direct capacity to kill cancer cells and has a potential antitumor effect. As the rising role of immune cells function in the tumor microenvironment (TME), ferroptosis may have additional impact on the immune cells, though this remains unclear. In this study we focus on the ferroptosis molecular network and the ferroptosis-mediated immune response, mainly in the TME, and put forward novel insights and directions for cancer research in the near future.